Variations in major quality parameters of forage and medium quality winter wheat varieties in storage - Mezei, Zoltán; Győri, Zoltán (Acta Agraria Debreceniensis, 2007)
We analysed five parameters (moisture-, protein content, Hagberg’s falling number, wet gluten content and alveographic W (10-4 J) values) and the microbiological changes of four forage and milling III. quality winter wheat varieties (Magor, Hunor, Róna and Kondor) during storage, to determine the tendency, type and volume of the of the change of this five qualitative parameters during storage. We found that the examined winter wheat varieties retained their moisture, protein content and their Hagberg’s falling number, they did not change during storage. A slight growth could be experienced in the values of wet gluten content for all the four winter wheat varieties in terms of the duration of storage (129 days). This result proved the theory of after-ripening, when gluten percentage improves qualitatively and quantitatively as well. The value of the quantitative growth was about 10% for all the four winter wheat varieties. We placed a special emphasis on measuring the alveographic W (10-4 J) values during storage. All the four winter wheat varieties showed decreasing values of about 20-40%. Microbiological examinations on the four winter wheat varieties showed that mould, mould flora and total germ count remained balanced with some slight variations and they did not change in terms of time under optimal storage conditions.